Impact of short-term discontinuation of ivermectin-based chemoprevention on onchocerciasis transmission in endemic settings with long history of mass drug administration. - Arnauld Efon-Ekangouo; Hugues C Nana-Djeunga; Narcisse Nzune-Toche; Raïssa Dongmo-Yemele; Jean Bopda; Viviane Ongbassomben; Laurentine Sumo; Anne Geiger; Thomas B Nutman; Joseph Kamgno (Public Library of Science (PLoS), 2023)
Background The control of onchocerciasis currently relies on annual distribution of single dose ivermectin. Because ivermectin has minimal effects on the adult parasite, mass drug administration (MDA) campaigns against onchocerciasis require at least 15 years of annual uninterrupted ivermectin distribution. Mathematical models have predicted that short-term disruption of MDA (as was seen during COVID-19) could impacted the microfilaridermia prevalence depending on the pre-control endemicity and the histories of treatment, requiring corrective measures (such as biannual MDA) to mitigate the effect on onchocerciasis elimination. Field evidence supporting this prediction, however, has yet to be gathered. This study aimed to assess the impact of ~2 years disruption of MDA on onchocerciasis transmission indicators. Methodology A cross-sectional survey was carried out in 2021 in seven villages of Bafia and Ndikinimeki, two health districts located in the Centre Region, Cameroon, where MDA has been ongoing for two decades, but interrupted in 2020 as a response to the COVID-19 pandemic. Volunteers aged 5 years and above were enrolled for clinical and parasitological examinations for onchocerciasis. Data were compared with pre-COVID-19 prevalence and intensity of infection from the same communities to measure changes over time. Principal findings A total of 504 volunteers (50.3% males), aged 5-99 years (Median: 38; IQR: 15-54) was enrolled in the two health districts. The overall prevalence of microfilaridermia in 2021 was similar in Ndikinimeki health district (12.4%; 95% CI: 9.7-15.6) and Bafia health district (15.1%; 95% CI: 11.1-19.8) (p-value = 0.16). Microfilaridermia prevalences were either similar between 2018 and 2021 in the communities of Ndikinimeki health district (19.3% vs 12.8% (p = 0.057) for Kiboum 1; and 23.7% vs 21.4% (p = 0.814) for Kiboum 2), or higher in 2019 compared to 2021 in the communities of Bafia health district (33.3% vs 20.0% (p = 0.035) for Biatsota). The mean microfilarial densities in these communities dropped from 5.89 (95% CI: 4.77-7.28) mf/ss to 2.4 (95% CI: 1.68-3.45) mf/ss (p-value < 0.0001), and from 4.81 (95% CI: 2.77-8.31) mf/ss to 4.13 (95% CI: 2.49-6.86) mf/ss (p-value < 0.02) in Bafia and Ndikinimeki health districts, respectively. Community Microfilarial Load (CMFL) dropped from 1.08-1.33 mf/ss in 2019 to 0.052-0.288 mf/ss in 2021 in Bafia health district while remaining stable in the Ndikinimeki health district. Conclusion/significance The continued decline in prevalence and CMFL observed ~2 years after MDA disruption is consistent with mathematical predictions (ONCHOSIM) and shows that additional efforts and resources are not needed to mitigate the effects of short-term MDA disruption in highly endemic settings prior to intervention with long treatment histories.